The Role of Citizenship Education in Forming Legal Awareness for Adolescents - Barokah, Aisha; Susanti, Emilia; Putri, Cindy Febriyani; Priska, Dearezha; Amri, Nadila (CV. Rayyan Dwi Bharata, 2024)
The role of Citizenship Education in forming legal awareness for teenagers in order to create a law-abiding society. Legal awareness helps individuals understand their rights and obligations and participate in law enforcement. Efforts to increase teenagers' legal awareness through citizenship education involve the integration of technology, criticism, open discussions, teacher training, legal counseling, legal reform, and law enforcement. Legal awareness and legal obedience are important in forming correct legal behavior, involving knowledge, attitudes and legal behavior patterns. Although Citizenship Education can help increase legal awareness in adolescents, challenges such as diverse interests, negative perceptions of the law, appropriate use of language, and connection to real life need to be addressed. Thus, citizenship education plays a key role in building the concept of law enforcement in the younger generation to prevent moral decline and face the challenges of globalization.